Kesehatan telinga mahasiswa Sekolah Polisi Negara Karombasan Manado - Timbuleng, Tamira T.; Palandeng, Ora I.; Pelealu, Olivia C.P. (e-CliniC, 2016)
Abstract: Ear is one of the five senses that functions as hearing and body balance device. The health status of human ear is influenced by lifestyle, activities, and environmental factors. Noise is one of the hazardous physical factors that could cause hearing problems ranging from temporary to permanent deafness depending on the intensity of noise, duration of exposure, and individual sensitivity towards noise. Ear health status can be determined through investigation problems or abnormalities of the ear and the hearing function. This study was aimed to obtain the profile of ear health among students of State Police Academy Karombasan Manado. This was a descriptive observational study with a cross-sectional design. There were 30 students as respondents. Data were analyzed by using Microsoft Excel 2010. The results showed that only one respondent (3%) had abnormal outer ear shape (preauricular fistula) meanwhile 29 respondents (97%) had normal outer ear shape. Based on the ear canal, 25 respondents (83%) had normal ear canal and 5 respondents (17%) had cerumen. Investigation of tympanic membrane showed that all respondents had normal tympanic membrane. All respondents had good ear function based on Rinne and Weber tests. Conclusion: Ear health status among students of State Police Academy Karombasan Manado was categorized as good.Keywords: ear abnormality, hearing function abnormalityÂ Abstrak: Telinga merupakan indera yang berfungsi sebagai alat pendengaran dan keseimbangan tubuh. Status kesehatan telinga manusia dipengaruhi oleh perilaku hidup, aktifitas, dan faktor lingkungan. Kebisingan merupakan salah satu faktor fisik yang dapat menyebabkan gangguan pendengaran mulai dari ketulian sementara sampai ketulian permanen bergantung pada intensitas, lama waktu paparan, dan kepekaan individu terhadap kebisingan. Status kesehatan telinga dapat ditentukan dengan pemeriksaan gangguan atau kelainan telinga, dan pemeriksaan gangguan fungsi pendengaran. Penelitian ini bertujuan untuk mendapatkan gambaran kesehatan telinga mahasiswa Sekolah Polisi Negara Karombasan Manado. Jenis penelitian ialah deskriptif observasional dengan desain potong lintang. Responden penelitian ialah 30 mahasiswa Sekolah Polisi Negara Karombasan Manado. Data hasil penelitian diolah menggunakan Microsoft Office Excel 2010. Hasil penelitian menunjukkan pada pemeriksaan telinga luar hanya 1 responden (3%) yang memiliki bentuk telinga luar abnormal yaitu fistula preaurikular, sedangkan 29 responden (97%) memiliki kondisi telinga luar normal. Pemeriksaan membran timpani mendapatkan hasil normal telinga kiri dan telinga kanan pada semua responden (100%). Pemeriksaan tes fungsi pendengaran Rinne dan Weber mendapatkan hasil normal pada 30 responden (100%) baik telinga kiri dan kanan. Simpulan: Status kesehatan telinga mahasiswa Sekolah Polisi Negara Karombasan Manado tergolong baik. Kata kunci: gangguan atau kelainan pada telinga, gangguan fungsi pendengaran